Hubungan Antara Tingkat Kecemasan Menghadapi Test Of English Proficiency (Toep) Dengan Hasil Toep Pada Mahasiswa Fakultas Psikologi Angkatan 2015 Universitas Muhammadiyah Surakarta - Putri, Dinda Edwinda; , Susatyo Yuwono, S.Psi, M.Si., Psi (2016)
TOEP is a test that is mandatory for all Bachelor of Muhammadiyah University of Surakarta students who have graduated in English I and English II. Recapitulation of the TOEP exam of Psychology Study Program Grade of 2013 and 2014 show the percentage of passing TOEP exams still below 50%. Previous study mentioned there are correlation significant achievement TOEP and anxiety level, where participants with lower test scores tend to experience higher levels of anxiety. Anxiety knocked reason, in anxiety levels are high, people are guided and directed by negative thinking and tend to be destructive. The purpose of this study was to determine the correlation between the anxiety level for the TOEP with the results of TOEP, the effective contribution of the anxiety level to face TOEP with the results of TOEP, levels in anxiety level to face TOEP and level results of TOEP. Hypothesis proposed was that there was a negative correlation between anxiety level to face TOEP of Physchology students grade of 2015 and results of TOEP in Muhammadiyah University of Surakarta. The method in this research used the quantitative method. The amount of the research subjects was 212 Physchology students grade of 2015 Muhammadiyah University of Surakarta. The methods of data collection used the scale of anxiety level and the documentation of results of TOEP. Meanwhile, the method of sampling used in this research was population study. The results of calculation using product moment, it was obtained the score of the coefficient of correlation (rxy) as much as -0,533 significance = 0,000; (p < 0,01), that meant that there was negatively significant correlation between anxiety level with the results of TOEP. The effective contribution of anxiety level on the results of TOEP as much as 28,4%. From the results of this research, it was also known that anxiety moderate level and the results of TOEP of Physchology students grade of 2015 were categorized as more basic abilities.